PENGGUNAAN MEDIA MICROSOFT SWAY TERHADAP KETERAMPILAN KOMUNIKASI PESERTA DIDIK PADA PEMBELAJARAN IPS DI SEKOLAH DASAR - Ahmad Jauharul Wadud; Fina Atifatul Husna; Mochamad Mas’ud Yunus Arifuddin; Ayu Zafira Ramadhani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the issue of students lacking active engagement in Social Studies (IPS) lessons, resulting in poor communication skills. The study aimed to examine the impact of using the interactive learning medium Microsoft Sway on improving the communication skills of fourth-grade students in Social Studies. A quantitative approach was employed, utilizing a quasi-experimental method with a non-equivalent control group design. Data collection techniques included questionnaires, observation, interviews, and documentation. Data analysis involved t-tests and the calculation of N-Gain scores. The t-test results showed that t-calculated > t-table (6.473 > 1.688); consequently, the null hypothesis (H0) was rejected and the alternative hypothesis (H1) was accepted. This indicates a significant difference in student communication skills resulting from the use of Microsoft Sway in fourth-grade Social Studies lessons at SD Siti Aminah Surabaya. N-Gain calculations revealed a score of 0.40 (moderate category) for the experimental class and 0.21 (low category) for the control class.